2008
DOI: 10.1017/s0047404508080998
|View full text |Cite
|
Sign up to set email alerts
|

Repair in membership categorization in French

Abstract: Using conversation analysis as methodology, this article provides a link between the local organization of talk and larger societal issues by investigating specific conversational sequences in which French speakers from different speech communities interact. It is argued that in addition to dealing with problems of speaking, hearing, and understanding, repair can simultaneously be used to negotiate linguistic membership. Repair can be used to establish, confirm, or insist on speakers' belonging to one particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The field of language and social interaction (LSI) generally agrees that analysis should closely focus on the particulars of language use (micro), but there is debate about how to connect analysis of language use to macro forms of social organization (Schegloff 1987; Billig 1999; Tracy 1999; Kitzinger 2000; Maheux-Pelletier & Golato 2008). Some argue analysts should illustrate how participants orient to the macro through their language use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field of language and social interaction (LSI) generally agrees that analysis should closely focus on the particulars of language use (micro), but there is debate about how to connect analysis of language use to macro forms of social organization (Schegloff 1987; Billig 1999; Tracy 1999; Kitzinger 2000; Maheux-Pelletier & Golato 2008). Some argue analysts should illustrate how participants orient to the macro through their language use.…”
Section: Introductionmentioning
confidence: 99%
“…Additional contributions to this study include demonstrating the utility of membership categorization analysis for analyzing discourses of racism and providing practical insight into how racially diverse groups can have productive conversations about racism. (Racism, ideology, membership categorization analysis)*The field of language and social interaction (LSI) generally agrees that analysis should closely focus on the particulars of language use (micro), but there is debate about how to connect analysis of language use to macro forms of social organization (Schegloff 1987;Billig 1999;Tracy 1999;Kitzinger 2000;Maheux-Pelletier & Golato 2008). Some argue analysts should illustrate how participants orient to the macro through their language use.…”
mentioning
confidence: 99%
“…As many scholars “have called for research that provides a link between micro and macro issues of language use” ( Maheux-Pelletier and Golato, 2008 , p. 689), in this study, we attempted to illustrate many implications that a discursive investigation of the local organization of a microcosm of talk (i.e., the use of social categorization markers and qualifying devices of groups during an ethnographical interview) has to illuminate a larger social issue, such as intergroup relations. We did so by originally focusing on an intensive group-care context, i.e., group homes for out-of-home children, which has been rarely investigated by group research.…”
Section: Discussionmentioning
confidence: 99%
“…In the first step of our analytical procedure, we listened multiple times to the original audio recordings and reread the transcripts, adjusting and finalizing the transcription process. In this phase, we also underlined the references that professionals made to intergroup relations, keeping in mind that “they are not preexisting outside discourse, but are ‘talked into being,’ that is, produced by the members to the interaction and can therefore be analyzed” ( Maheux-Pelletier and Golato, 2008 , p. 690). To investigate intergroup relation discursive accomplishment, for the purpose of this study, we focused exclusively on two discursive devices that we detected during this analytical phase, namely, social categorization markers and qualifying devices.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a survey of a large number of language program directors at North American universities, and this survey revealed that a small number of teaching methodology textbooks (including Brandl 2008;Larsen-Freeman and Anderson 2011;Lee and VanPatten 2003;Loewen 2014;Kumaravadivelu 2006) are widely used in French, German, and Spanish language teaching methods courses. It is important to note that the view of language we find in these texts is grounded primarily in psycholinguistic research in second language acquisition.…”
Section: Views Of Language In Methods Textbooks and Proficiency Frameworkmentioning
confidence: 99%